Controle estatístico e previsão do monitoramento do índice de qualidade da água - Conceição, Ketllin Zanella da (2017)
The unplanned development of large urban centers as well as the industrial one have hindered sustainable awareness regarding the correct water application. The unruly use of this resource has drawn the scientific community attention, thus, several scientific trials have been carried out in order to evaluate the use and quality of water. The use of indicators is one of the possibilities to evaluate water quality, which aims at analyzing physical-chemical and biological characteristics, and so allowing the evaluation of water body quality. In order to quickly evaluate the parameters involving water quality index (WQI), the process capability index was used. Thus, this trial aims at determining the water quality index as well as applying statistical quality control methodologies to evaluate the monitoring of water quality in rivers. Therefore, a database with physical-chemical and microbiological parameters from Passaúna and Piraquara rivers was applied to carry out this research development. Those rivers are in Araucária and Piraquara cities, respectively. The water quality index was determined by the time series, and subsequently data were submitted to statistical process control, with Shewhart individuals, EWMA and CUSUM, control charts as well as the development of the process quality index. Based on these data, a model of forecast was developed according to Holt-Winters Additive method. The WQI detected that the studied rivers remained under an averaged quality until the year of 2000, however, since that year, it was possible to observe a decreasing trend in water quality of the evaluated rivers. This trend was also identified by control charts. The graphs were also able to identify that waters of the rivers were not under statistical control, identifying some points that exceeded the used control limits. The process capacity index showed that the Piraquara River was classified with better quality of water when compared to the Passaúna River. The Holt-Winters prediction method showed that both rivers would continue with a decreasing trend in WQI and consequently in water quality. The applied statistical tools proved to be fast and efficient to evaluate water quality control. Finally, it is suggested that other researches should be developed using the technique of statistical process control for environmental evaluation.